Inclusive principles and practices in literacy education - Milton, Marion (Emerald Publishing, 2017)
This volume draws together research and practice from the fields of literacy education and inclusion. It provides an insight into current theory, research and issues associated with teaching literacy to all students in inclusive classrooms. Literacy remains a critical success factor for students, as the basis for concurrent and future learning.
Keywords: Literacy -- Study and teaching.; elektronické knihy; electronic books